A nano-scale instability in the β phase of dilute Ti–Mo alloys. (15th April 2016) - Zheng, Yufeng; Banerjee, Dipankar; Fraser, Hamish L.
Abstract: A nano-scale instability in the β phase resulting in the formation of the disordered orthorhombic O′ phase has been discovered in a fairly dilute binary Ti–Mo alloy, using selected area electron diffraction and high resolution scanning transmission electron microscopy. The O′ phase is formed in the alloy when the Mo content exceeds a critical value. The instability occurs in β-solutionized samples that have been quenched to room temperature and is found to co-exist with athermal ω phase. Interestingly, this nano-scale instability, involving the 110 < 1 1 ¯ 0 > soft-phonon shuffle, occurs in the β phase without deliberate additions of either interstitial or substitutional solutes. Graphical abstract: